Bridging the Expectation Gap of the Institutional Donors and Charity Management: Preliminary Insights Evidence - Saunah Zainon; Ruhaya Atan; Yap Bee Wah (Journal of Accounting, Business and Management (JABM), 2012)
It is commonly believed that donors would donate more to charity if they were assured that the funds will be utilised properly and not wasted. Evidence from previous literature also shows that the donors tend to give more support and contribution to the charity if they were equipped with charity information. As far as the charity sector is concerned, the core competency of the charity sector is to build strong relationships with donors. Their ability to build this relationship will contribute to a strong sustainable income for the charity to operate. In Malaysia, there is no avenue for the stakeholders, particularly the donors as the key stakeholders to obtain information on charity especially with regard to the financial information. This study seeks to develop insights into institutional donors? expectations and the information that charities offers, bridging the expectation gap between the donors and the charity management. Insights evidence, both from the donors and the charity management were provided in order to bridge the gap between the donors? expectations and the charity management?s offers of information, so as the result can be used for better charity reporting in the future. The finding shows that both financial and non-financial information are seen as important by the institutional donors but not the major criterion concerned by the charity management. This study tries to fill the gap.